2009
DOI: 10.3899/jrheum.071229
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Disability in Patients with Treatment-Failure Gout

Abstract: Severe gout is associated with poor HRQOL and disability, especially for patients who experience more gout flares and have a greater number of involved joints. Subject perceptions of gout-related functioning and pain severity appear to be highly sensitive indicators of HRQOL and disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
122
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(136 citation statements)
references
References 17 publications
10
122
0
4
Order By: Relevance
“…RCG is a severe form of arthritis with signs and symptoms that may include frequent and prolonged flares, presence of tophi, chronically tender and swollen joints, and impaired physical function and health-related quality of life (HRQOL) 1 . Refractory disease is estimated to occur in roughly 120,000 of the 3 million to 6 million Americans who experience gout based on a recent comprehensive market research study (unpublished data, Savient Pharmaceuticals Inc.).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RCG is a severe form of arthritis with signs and symptoms that may include frequent and prolonged flares, presence of tophi, chronically tender and swollen joints, and impaired physical function and health-related quality of life (HRQOL) 1 . Refractory disease is estimated to occur in roughly 120,000 of the 3 million to 6 million Americans who experience gout based on a recent comprehensive market research study (unpublished data, Savient Pharmaceuticals Inc.).…”
mentioning
confidence: 99%
“…The clinical course and therapeutic management of patients with RCG can be further complicated by the presence of significant medical comorbidities, most commonly hypertension, metabolic syndrome, chronic kidney disease, and osteoarthritis (OA), and less frequently cardiovascular disorders and diabetes 1 . Epidemiologic studies show that these patients are at increased risk of both cardiovascular events and all-cause mortality 2 .…”
mentioning
confidence: 99%
“…Gout prevalence increases with age, affecting 12.6% of those aged 80 and over 1 . Untreated and undertreated gout progresses to a chronic disabling arthropathy in a significant number of patients 2 . An increasing proportion of patients with gout have complex profiles of comorbidities and long prescription medication lists further complicating their management 3 .…”
Section: The Real World Of Goutmentioning
confidence: 99%
“…Recently, several papers assessed the influence of gout on health-related quality of life (HRQOL) among various study populations using different definitions of gout (Table 1) [24][25][26][27][28][29][30][31][32] . These studies often employed generic HRQOL instruments such as the Medical Outcome Study Short-Form 36-item health status survey (SF-36) [26][27][28][29][30]32 and/or the Health Assessment Questionnaire-Disability Index (HAQ-DI) [24][25][26]29 and only 2 previous studies evaluated the potential utility of a diseasespecific HRQOL measure for gout called the Gout Assessment Questionnaire (GAQ) 27,28 . HAQ-DI scores from these studies suggested gout patients have mild disability (HAQ score range, 0.2 to 0.6) 24,25,29 .…”
mentioning
confidence: 99%
“…In this issue of The Journal, Becker and colleagues report on a multicenter, prospective observational study examining this issue 26 . The authors evaluated self-reported quality of life, disability, and disease severity among patients with "treatment-failure gout."…”
mentioning
confidence: 99%